The Cambridge companion to Merleau-Ponty - Carman, Taylor; Hansen, Mark B. N. (Cambridge University Press, 2005)
Maurice Merleau-Ponty (1908-61) was described by Paul Ricoeur as 'the greatest of the French phenomenologists'. The essays in this volume examine the full scope of Merleau-Ponty's philosophy, from his central and abiding concern with the nature of perception and the bodily constitution of intentionality to his reflections on science, nature, art, history, and politics. The authors explore the historical origins and context of his thought as well as its continuing relevance to contemporary work in phenomenology, philosophy of mind, cognitive science, biology, art criticism and political and social theory. What emerges is a fresh image of Merleau-Ponty as a deep and original thinker whose philosophical importance has been underestimated, in part owing to the influence of intellectual movements such as existentialism and structuralism, into which his work could not be easily assimilated. New readers will find this the most convenient and accessible guide to Merleau-Ponty currently available.